Optimal quantum channel estimation of two interacting qubits subject to decoherence - Zheng, Qiang; Yao, Yao; Li, Yong (The European physical journal. D, Atomic, molecular, and optical physics, 2014)
We investigate the estimation of the quantum channel parameter for a two-qubit system with each qubit independently interacting with its Markovian environment. The dynamics of quantum Fisher information in this system is studied and employed as a measure to quantify the precision of the estimation. We find that the dynamic behavior of quantum Fisher information with respect to the decoherence rate γ is proportional to t 2 /[exp( γt ) − 1] and exp(−2 γt ) in the unitary limit and the completely decoherent limit, respectively. We also study the evolution of quantum Fisher information with respect to the interaction strength, which shows oscillating behavior. Furthermore, we show that the increase in entanglement of the input state may not enhance the precision of quantum estimation.